Activating Mutation of SHP2 Establishes a Tumorigenic Phonotype Through Cell-Autonomous and Non-Cell-Autonomous Mechanisms - Dong, Lei (Front Cell Dev Biol, 2021)
Gain-of-function mutation of SHP2 is a central regulator in tumorigenesis and cancer progression through cell-autonomous mechanisms. Activating mutation of SHP2 in microenvironment was identified to promote cancerous transformation of hematopoietic stem cell in non-autonomous mechanisms. It is interesting to see whether therapies directed against SHP2 in tumor or microenvironmental cells augment antitumor efficacy. In this review, we summarized different types of gain-of-function SHP2 mutations from a human disease. In general, gain-of-function mutations destroy the auto-inhibition state from wild-type SHP2, leading to consistency activation of SHP2. We illustrated how somatic or germline mutation of SHP2 plays an oncogenic role in tumorigenesis, stemness maintenance, invasion, etc. Moreover, the small-molecule SHP2 inhibitors are considered as a potential strategy for enhancing the efficacy of antitumor immunotherapy and chemotherapy. We also discussed the interconnection between phase separation and activating mutation of SHP2 in drug resistance of antitumor therapy.